The Construction of Religious Identity of the Crusades: Historical Legacy in Contemporary International Relations - Hilmi Pauzian, Muhamad (UIN Sunan Gunung Djati Bandung, 2025)
The Crusades (1095-1291) were one of the most complex historical phenomena in the history of international relations, creating patterns of conflict and peace that continue to influence global dynamics to this day. This research aims to analyze how the construction of religious identity, enemy perceptions, and the legacy of violent/peaceful rhetoric from the Crusades shaped contemporary international relations patterns. Using Alexander Wendt's constructivist theoretical approach, this study applies a qualitative method with historical analysis and discourse to Crusade historical documents, political speeches, diplomatic narratives, and foreign policy. The results of the study show that the Crusades not only created a polarized religious identity between Christianity and Islam, but also resulted in innovative mechanisms of diplomacy and peace through trade agreements, strategic alliances, and cultural exchanges. Key findings reveal that the legacy of the Crusades has been internalized in the cognitive structures of international actors, shaping perceptions of threats and opportunities in West-Middle East relations. The conclusions of this study show that the understanding of the social construction of identity and norms rooted in the Crusades makes a significant contribution to the analysis of contemporary international relations, especially in understanding the dynamics of conflict and peace in the Middle East region and cross-civilizational relations.